MASS MEDIA IN A PANDEMIC PERIOD (A Case Study of Radio in Surakarta-Indonesia) - kartinawati, erwin (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2024)
This study examined the mass media condition, especially radio in Surakarta or Solo City, during the COVID-19 pandemic. The research used qualitative methods, technically by interviews, observations, and documents studied on public, private, and community radio. The results show that the COVID-19 pandemic has impacted the media industry, including radio. We could see from the changes in broadcast aspects, advertising orders or financial conditions, and human resource aspects. The pandemic required broadcasters to make changes to broadcasts, both changes in broadcast duration and changing agendas and changes in broadcasters' work schedules. In the financial aspect, broadcasting institutions with government financial sources did not get significant shocks. Still, private broadcasters suffered heavy losses due to loss of sponsorship and off-air activities. Media workers also got impacts ranging from exposure to death. Non-public media workers also affect late payments to salary reductions due to the pandemic